A Comparative Study of Humility according to the Levels of Attribution Error among the Heads of Departments at Al-Qadisiyah University - Johni, Ahmed Abdulkadhim (Al-Adab Journal, 2022)
The results of many researches and studies indicated that one of the reasons for failure in different organizations is the personal crises among some of their employees, including the study of Sankar (2000) whose results confirmed that the crisis of the collapse of leading organizations and companies during the nineties was a natural result of the arrogance, selfishness and narcissism of their leaders; therefore, they made wrong decisions that helped in the collapse of their organizations without neglecting the effects practiced by technological, social, economic and cultural changes in this. Accordingly, one of the important trends that characterized contemporary psychology to overcome these problems is the study of positive traits in people (in order to make the right person in the right place of work), including humility, as the humble people are less likely than narcissists and arrogant people to engage in manifestations of self-conceit and excessive focus on it, as the humble ones can see the success, failure, work and behavior of others without exaggeration, but this does not mean that they may have bias towards the behaviors of others. Based on that, this research came as a comparative study in humility according to the levels of attribution error among the heads of department. On a sample of (100) heads of departments chosen randomly. To measure this, a scale was prepared to measure humility, which in its final form consisted of (20) items to be answered according to a five-point gradation of response (Likert method), and another scale was prepared to measure the attribution error which in its final form consisted of (9) attitudes. After extracting the indicators of validity and reliability for both scales using the appropriate statistical methods, the results of the research indicated that the heads of departments enjoy humility and have no error in the attribution. The research ended up with some recommendations and suggestions.